Chitosan suspension as extractor and encapsulating agent of phenolics from acerola by-product. (November 2022) - Silva, Natalia Cristina da; Assis, Odílio Benedito Garrido; Sartori, Alan Giovanini de Oliveira; Alencar, Severino Matias de; Martelli-Tosi, Milena
Graphical abstract: Highlights: Phenolic acids and flavonoids are extracted and encapsulated in chitosan suspension. The phenolic encapsulation efficiency is proportional to the chitosan concentration. Possible hydrogen and electrostatic interactions occur between chitosan-phenolics. Phenolics do not change the stability of chitosan nanoparticles. Active release from chitosan nanoparticles depends on the pH. Abstract: The polymeric suspension of chitosan (Ch) has been an effective media for the extraction of total phenolic compounds (TPC) from the acerola by-product. It facilitates the subsequent production of nanoparticles loaded with the phenolics (Np-TPC) by ionic gelation. However, neither the effects of Ch concentration on encapsulation efficiency (EE%) of TPC nor which compounds are extracted in its media are known, being it the first objective of this study. The second objective was to analyze the stability of the Np-TPC under accelerated conditions and its release profile at pHs 3.0 and 7.0. The results showed that Ch does not affect the extraction of TPC. However, the EE increased from 35.0 to 48.1 % with the increase of Ch concentration (0.4 to 1.0 %). LC/ESI-QTOF MS analysis showed that phenolic acids and flavonoids are extracted in 0.8 % Ch medium. After encapsulation, microscopy images revealed particle sizes ranging between 110 and 150 nm. Additionally, the presence of phenolics did not change the stability of the particles under accelerated conditions and the actives were fully released into the released medium for 10 h. The Np-TPC suspension appears to be useful for the production of edible antioxidant coatings to preserve fruits/vegetables, with potential application as carrier of other food ingredients.